2021
DOI: 10.3390/jal2010001
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic Determinants, Health Conditions, and Mental Status as Predictors of the Functional Status of Older Saudi People

Abstract: The increasing population of Saudi elderly demands adequate assessment of their functional health status and mental status to improve their health and quality of life. This study aimed to determine the functional status of older Saudi people in performing basic activities of daily living (ADLs) and instrumental activities of daily living (IADLs) and its influencing factors. This quantitative, descriptive-correlational study surveyed a total of 203 participants using the Mini-Mental State Examination, Katz Inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Another recent study by Al Anazi had 203 respondents with a mean age of 72.3 years. Over half (52.71%) of the participants were female, aged 65 years and older, extending beyond 75 years [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Another recent study by Al Anazi had 203 respondents with a mean age of 72.3 years. Over half (52.71%) of the participants were female, aged 65 years and older, extending beyond 75 years [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the participants aged between 65 and 75 years had the highest independence level in the Katz ADL and Lawton-Brody IADL, whereas those aged 85 years and older showed declined performance in ADL and IADL. This can be attributed to the aging process, having multiple chronic diseases, and frailty [ 10 , 14 , 21 ]. Other studies have also reported functional decline associated with the age of 85 years or more [ 10 , 14 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations